Political Economy of Labour Market Institutions in a Globalised Era - Sumon K. Bhaumik; Richard Frensch; Stephan Huber (Institute of Labor Economics (IZA), 2021)
The paper extends the literature on the political economy of labour market institutions by developing a framework in which owners of capital can benefit from both greater labour market flexibility and better rule of law. Their choice of location of manufacturing centres can, therefore, by influenced both by reduction in expropriation that is associated with better rule of law and greater bargaining power vis-à-vis workers by way of greater labour market flexibility. It follows that where owners of capital are better placed to influence government choices of these institutions, labour market flexibility is influenced by both labour market institutions intensity of exports and as well as rule of law intensity of exports. These predictions are borne out by a cross-country empirical analysis.
Keywords: D72; J41; 330; labour market institutions; political economy; globalisation